A regulação jurídica do uso da soja no Brasil por parte das empresas transnacionais - Gonçalves, Walker (2024)
The search for social capitalism, genuinely and effectively concerned with the well-being of society as a whole, with social guarantees for citizens, decent employment and income, minimum food security, respect for human rights, sustainable socio-environmental economic development, imposes regulation economic activity in general, and especially transnational relations, including the production and export of agricultural commodities, especially the main one, soybeans, given the scenario of constant and dynamic changes in economic relations experienced in Brazil and in different countries. Consistent and well-balanced regulation and control over the production and export of soybeans as the main agricultural commodity, could prove to be an important factor in a shift towards a more humanistic development, with gains in social rights for the national people, access to their own food and various consumer products that use this raw material in their compositions and productions. The scenario in which we experience deregulation of the market for this commodity implies food overinflation and food insecurity and hunger among Brazilian citizens. Almost all of this fresh product, which serves as the basis for many processed foods, is exported, generating a shortage in the supply of the domestic market and the consequent overprice of foods, from the most basic to the most refined. The objective is to demonstrate how serious and efficient regulation of this market can contribute to a reduction in food prices and also function as a gain in employment and income for Brazilian citizens, as well as a sustainable use of soil and subsoil, with conservation and preservation from nature. It was realized that this regulation of the use of transnational soybeans can contribute to progress towards a humanist, social, sustainable capitalism, equalizing relationships and interests, improving income distribution and social justice, achieving development with a general improvement in the quality of life of people, compliance with the company's social function and corporate social responsibility, and control of internal food prices, reducing the country's hunger scenarios. As for the work methodology, the inductive approach was used, seeking a conclusion, based on the observation of data, knowledge, own literature and existing experiences. The procedural method was comparative, checking the data, elements, experiences and knowledge, in order to investigate and reflect on their distinctions, tangencies, connections, continences and similarities. The research, study and analysis adopted the technique of bibliographic and documentary research in the areas of International Economic Law, Regulation Law, Economics, Economic Environmental Law, Social and Human Rights and General and Legal Sociology.